A model for fostering creativity in the product development process. Issue 2 (3rd April 2021) - Carmona Marques, P.
ABSTRACT: The present paper illustrates a pilot experiment in which a new model for fostering creativity in the product development process is tested with novice engineers. After introducing creativity in the field of product development, the current author presents the new standard. The theoretical background that embodies the new model is presented, based on relevant literature. Making use of the new model, a methodology for testing it, using novice engineers is then proposed. It relies on the comparison between novices that were trained in the model in comparison to other novices that were not trained in the model. Higher results for creativity achieved by novice engineers that have employed the model show the advantages of its application during product development activities.